Prediction of Blood Flow Velocity and Leaflet Deformation Via 2D Mitral Valve Model - Mohd Azrul Hisham, Mohd Adib; K., Kadirgama; N.H, Mohd Hasni; K., Osman; O., Maskon (Faculty Mechanical Engineering, UMP, 2012)

(untitled)
In the mitral valve, regional variations in structure and material properties combine to affect the biomechanics of the entire valve. Previous study, we know that mitral valve leaflet tissue is highly extensible. A two-dimensional model of the mitral valve was generated using an Arbitrary Lagrangian-Eulerian (ALE) mesh. A simple approximation of the heart geometry was used and the valve dimensions were based on measurements made. Valve open and closure was simulated using contact equations. So, the objective of this study was to investigate and predict flow and leaflet phenomena via simple 2D mitral valve model based on critical parameter of blood. Two stages of mitral valves analysis systolic and diastolic stages were investigated. The results show linear correlation between rigidity of the mitral valves leaflet and volume of backflow. Also the simulation predicted mitral valve leaflet displacement during closure agreed with our previous data analysis results and the results for blood flow velocity during systole condition through the mitral valve outlet as reported in the medical literature. In conclusions, these computational techniques are very useful in the study of both degenerative valve disease and failure of prostheses and will be continue developed to investigate heart valve failure and subsequent with surgical repair.